A Novel Hybrid Routing Algorithm with Two Fish Approach in Wireless Sensor Networks - Bhalaji, N. (Journal of Trends in Computer Science and Smart Technology, 2020)
Over the years, Internet of Things has advanced greatly advanced with technological inventions, enabling the development of smart networks globally. Network edge is introduced into the architectures in order to provide better user experience and quality of service But the issue with this these systems should be able to resist the attacks from external sources. There are many existing methods which are concerned with detecting the intrusion over static wireless sensor web. Due to various transmission regions being involved when using the sensor nodes, it is challenging task to choose the right guard nodes and sensor monitoring nodes. In order to address this issue, we propose a safe monitoring and routing protocol that incorporates Artificial intelligence on the basis of Authentication and Encryption Model. Analysis of the proposed work shows that it proves to be more efficient when compared to other routing and monitoring methods.
Keywords: Artificial Intelligence; Smart Network; Internet of Things; Secure Routing and Monitoring; Guard Nodes